THE ECONOMICS OF SECURITY AND DEFENCE. TRANSFER OF KNOWLEDGE AND INNOVATION RELATED TO THE DEFENCE INDUSTRY (Journal of the Spanish Institute for Strategic Studies, 2018)
The objective of this paper is to provide a definition of the economics of security and defence and its basis within the framework of a research study in companies belonging to the defence industry. It will analyse the security and defence economy and cooperation relationships among organisations, which were the subject of our doctoral thesis. One of the key points addressed in the article highlights defence’s role as an agent of Research, Development and Innovation (R&D&I).